2023
DOI: 10.12911/22998993/163494
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effect of Biological Growth-Regulating Preparations on the Yield of Agricultural Crops under the Conditions of Steppe Zone

Abstract: Increasing the production of high-quality agricultural products with minimal negative impact on environmental components is one of the priority tasks of modern agriculture. Due to the global world trends aimed at ensuring a sustainable and safe economy and reducing the use of chemical protection agents, it is predicted that the share of alternative biological methods in the European agricultural sector will increase to 10%, the area of agricultural land for organic farming will increase by 50%. Under the condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This crop rotation considers the specialization of the farm, all crops are placed after the optimal predecessors (Skok et al, 2023). The farm has its own canning shop, where a line for the production of canned peas from vegetable peas -TM "Green Peas" -has been preserved.…”
Section: Methodsmentioning
confidence: 99%
“…This crop rotation considers the specialization of the farm, all crops are placed after the optimal predecessors (Skok et al, 2023). The farm has its own canning shop, where a line for the production of canned peas from vegetable peas -TM "Green Peas" -has been preserved.…”
Section: Methodsmentioning
confidence: 99%
“…The Impact of Pre-Crops on the Formation of Water Balance in Winter Wheat Agrocenosis and Soil Moisture in the Steppe Zone Vitalii Pichura 1 , Larysa Potravka 1 , Yevhenii Domaratskiy 2* , Nataliia Nikonchuk 2 , Mykola Samoilenko 2 aimed at improving their productivity (Bruns, 2012;Siddique et al, 2021) that has become a cause of increasing genetic homogeneity and similarity of agricultural landscapes (Hufnagel et al, 2020;Sehgal et al, 2023). It was established (USDA-ERS… 2012; Skok et al, 2023) that application of balanced systems of crop rotations involving rotation of crops with high and low levels of residues in one field is an important method for coping with such problems. Crop rotations including legume crops contribute to an increase in productivity of a subsequent crop, maintaining nitrogen balance due to its fixation in soil (Claassen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is a determinant of the development of the agricultural sector of Ukraine's economy since it affects the volume and structure of agricultural production costs [1][2][3][4]. Therefore, agricultural crop varieties and hybrids adapted to climate change with advanced cultivation technologies become topical [5][6][7]. The research found that, under conditions of an increase in the air temperature, the Western and the Central Forest Steppes, Right-bank Ukraine, and Donetsk sub-zone of the Northern Steppe of Ukraine will be favorable areas for growing sunflowers [8].…”
Section: Introductionmentioning
confidence: 99%